CONCEPTUAL EXPLORATION OF COMMUNICATION AUDIT: URGENCY, PURPOSE AND IMPLICATIONS FOR ORGANIZATIONS - Fauzan Kurniawan; Reyhan Rafli Arya Saragih; Shalda Azka Qarina (Academic Solution Publisher, 2026)
A communication audit is an assessment activity conducted to determine the extent to which communication processes within an organization are running effectively. Good communication is a crucial factor in supporting cooperation, information delivery, and the achievement of organizational goals. This article aims to examine the concept of a communication audit, focusing on the importance of conducting the audit, the objectives to be achieved, and its impact on the organization. The article was written using a literature study method by reviewing various scientific sources, such as relevant books and journals. The results of the study indicate that a communication audit can help organizations identify various obstacles in information delivery, assess the effectiveness of communication channels, and identify communication gaps that occur. In addition, a communication audit also serves as a basis for improving the quality of communication, both internally and externally. The implementation of a communication audit provides various benefits, such as increased work efficiency, quality of coordination, satisfaction of organizational members, and the effectiveness of overall organizational management. Therefore, a communication audit can be seen as an important evaluation tool to support organizational development and improve the achievement of goals more optimally.